Peningkatan Kompetensi Guru melalui Pelatihan PhET Simulation bagi Guru MGMP Fisika Kabupaten Serang - Yoga Budi Bhakti; Irnin Agustina Dwi Astuti; Dasmo Dasmo (IKIP PGRI Bojonegoro, 2019)
This program is aimed to increase teacher competency through PhET simulation training. This activity is expected to be used as reference material for teachers to implement practical simulations that caused by time constraints and incomplete laboratory facilities and laboratory facilities. Community service activities are carried out using training, discussion, and mentoring methods. Based on the results of this program, 76.9% of the training participants really need knowledge of laboratory management. The trainees looked at the PhET simulation material as very relevant to the field of physics. This is proofed by a response of 76.9% which states that the PhET simulation material is very relevant to learning physics. The trainees also rated very well (92.3%) the benefits of the knowledge of the use of this media in the physics learning process. This training can be reference for trainees to carry out practicum activities virtually in their respective schools. The trainees found of that PhET simulation easy to understand. This condition can be seen from the results of a survey which stated that 92.3% of the training participants answered that it was easy to understand this material.Keywords: Phet Simulation, Physics, Teacher Competency Improvement, Virtual Laboratory.ABSTRAKÂ Program ini bertujuan untuk meningkatkan kompetensi guru melalui pelatihan PhET simulation. Kegiatan ini diharapkan dapat dijadikan bahan rujukan bagi guru untuk menerapkan simulasi praktikum yang disebabkan oleh keterbatasan waktu dan belum lengkapnya prasarana dan sarana laboratorium praktikum. Kegiatan pengabdian kepada masyarakat ini dilakukan dengan menggunakan metode pelatihan, diskusi, dan pendampingan. Berdasarkan hasil program ini, 76,9% peserta pelatihan sangat membutuhkan pengetahuan pengelolaan laboratorium. Peserta pelatihan memandang materi PhET simulation sangat relevan dengan bidang fisika. Hal ini dibuktikan dengan respon sebesar 76,9% yang menyatakan bahwa materi PhET simulation sangat relevan dengan pembelajaran fisika. Peserta pelatihan juga menilai sangat baik (92,3%) terhadap manfaat pengetahuan penggunaan media ini pada proses pembelajaran fisika. Pelatihan ini bisa menjadi acuan bagi peserta pelatihan untuk melaksanakan kegiatan praktikum secara virtual di sekolah masing-masing. Peserta pelatihan menilai PhET simulation mudah dipahami. Kondisi ini terlihat dari hasil survei yang menyatakan 92,3% peserta pelatihan menjawab mudah dalam memahami materi ini.Kata Kunci: Phet Simulasi, Fisika, Peningkatan Kompetensi Guru, Laboratorium VirtualÂ